Kinerja Keuangan Bank Terhadap Pertumbuhan Laba Pada Bank Umum Syariah Periode 2018-2020 - Aniek Murniati (Program Studi Akuntansi - STIE Kesuma Negara Blitar, 2022)
The growth performance of the Islamic banking industry has recently recorded an increase, including improvements in terms of non-performing financing (NPF), but sometimes conditions are unstable due to fluctuations in the increase and decrease in the performance of some Islamic banking such as CAR. This study aims to examine the performance of Islamic banks on profit growth. This research was conducted using a quantitative method on the financial statements of Islamic banking registered with the OJK in 2018-2020. The sampling technique used was purposive sampling method. The performance of Islamic banks is measured by the variables of NPF (Non Performing, Financing), FDR (Financing to Deposit Ratio), and CAR (Capital Adequacy Ratio). The results of the study simultaneously show that the variables of non-performing financing (NPF), financing deposit ratio (FDR), capital adequacy ratio (CAR) have a simultaneous effect on the dependent variable, namely profit growth. Partially the variables that affect profit growth are non-performing financing (NPF) and capital adequacy ratio (CAR).